(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article gives information about modern culturally developing girls who achieve good results in sports, the growth of physical education among women, clubs organized in many sports, Uzbek girls in sports schools in the central sections and information on the conditions given to them.